Impacts of Small-Scale Mechanized Logging Equipment on Soil Compaction in Forests - Varol, Tugrul; Emir, Tuna; Akgul, Mustafa; Ozel, Halil Baris; Acar, Hafiz Hulusi; Cetin, Mehmet (Springer Science and Business Media LLC, 2020)
The present study focuses on assessing the effects of different numbers of skidders on soil compaction. To assess the skidding effects, four-wheeled small-scale logging equipment attached to an ATV (Automated Transfer Vehicle) was used. Skidding operations were carried out on undistributed forest corridor (20 × 3 m).To measure soil compaction, 11 measurement lines were used, spaced at 2-m intervals. A total of 33 measurement points were used to measure soil compaction. Soil compaction values were measured for different soil depths with 5 cm intervals in the 0–40 cm range as MpA. The results were evaluated for the skidding zone and the wheel zone. Prior to skidding, soil compactions at 0 cm (top soil) is almost 2.5–3 times lower than those at the other depths. The p values indicate that the numbers of passes and the compaction values belong to nonidentical groups. The Bonferroni method was used to determine whether the compaction values are similar. The Dunn test results demonstrate that there were statistically significant differences between the mean values of the number of passes up to the 60th pass. However, there are no statistically significant differences between the means of the compaction values occurring between 60 and 80 and 100 and 120 passes. Generally, soil compaction is expressed as an increase in the soil bulk density. Soil bulk density and soil porosity are negatively correlated. It was found that for each of the zones, soil compaction values between the depths of 15 cm and 40 cm are approximately 4 times higher than at the 0 cm soil depth. Soil compaction values increased 3 times at the depths of between 0 cm and 5 cm. The average soil compactions values in the skidding zone are approximately 1.5 times higher than those at the wheel zones at the depth greater than 5 cm. The use of different skid trails will decrease soil compaction of the forest stand, provide uniformity of soil compactions in forest stand.
Keywords: Skidding; Amasra Forest District; Forest soil; Mechanized logging equipment; Compaction; Forest Soil; Plant Science; Mechanized Logging Equipment; 15. Life on land